Art, historical structural heterogeneity, time and the horizon of meaning - Ortiz Fernández, Carolina (2019)
On this occasion, I make an approach to his reflection on the structural historical heteroge- neity category, the time and importance of art in his work in dialogue with some passages of Quijano’s biography.